Penggunaan Algoritma Fuzzy Simple Additive Weighting (F-Saw) Sebagai Pendukung Keputusan Dalam Prioritas Pembagian Zakat Fitrah - Muhammad Daffa Arifin; Wahyu Syaifullah JS; Muhammad Muharrom Al Haromainy (Concept: Journal of Social Humanities and Education, 2024)
Zakat fitrah is an obligation for every capable Muslim to purify oneself and one's wealth. Determining the priority of zakat fitrah recipients often becomes a challenge due to various factors that must be considered. This research aims to use the Fuzzy Simple Additive Weighting (F-SAW) algorithm as a decision support tool in determining the priority for distributing zakat fitrah. By using the F-SAW method, it is hoped that the prioritization process can be more objective and efficient..